Challenging Analogy: Levinas, Maimonides, and Language Addressing Transcendence - Wolosky, Shira (Harvard theological review, 2025)
Emmanuel Levinas’s philosophy of absolute transcendence has been criticized for defeating any possibility of relationship to the divine as Other. Such critiques restage central theological trends that rely on analogy as opening just such an avenue to the divine. Aquinas proposes analogy in his own criticism of Maimonides’ negative theology of God as beyond any likeness, in ways similar to arguments leveled against Levinas. Levinas, however, proposes a language model, which also illuminates Maimonides’ own language discourses, as a way to allow relationship while sustaining distinction from transcendence. Through language, the divine is addressed while respecting absolute Otherness, in a move away from ontology to ethics.